2022
DOI: 10.2196/35173
|View full text |Cite
|
Sign up to set email alerts
|

Self-care Behaviors and Technology Used During COVID-19: Systematic Review

Abstract: Background Self-care behaviors are essential for people living with chronic conditions; however, the outbreak of the COVID-19 pandemic has imposed additional complications on their daily routines. Few studies have analyzed how self-care behaviors have changed during COVID-19 and the role of digital technology, especially among people with chronic conditions. Objective This study aims to review how self-care behaviors have changed for people with chronic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…During the lockdown period, patient associations were forced to suspend their activities, which increased isolation for patients with long-term diseases. Finally, our study shows the impact of the pandemic on recommended diet and physical activities, which is consistent with other studies reporting on self-care measures [64,65]. Lockdown measures such as stay-at-home orders and quarantine often limited opportunities for physical exercise and increased sedentary behavior, as well as changes in dietary patterns such as increases in overeating [66,67].…”
Section: Discussionsupporting
confidence: 91%
“…During the lockdown period, patient associations were forced to suspend their activities, which increased isolation for patients with long-term diseases. Finally, our study shows the impact of the pandemic on recommended diet and physical activities, which is consistent with other studies reporting on self-care measures [64,65]. Lockdown measures such as stay-at-home orders and quarantine often limited opportunities for physical exercise and increased sedentary behavior, as well as changes in dietary patterns such as increases in overeating [66,67].…”
Section: Discussionsupporting
confidence: 91%
“…According to their findings, in a developing country with the restricted resources, the condition can be worsened and significant loss of visits and increase in the number of postponed, cancelled, and delayed visits can be intensified mainly due to higher frequency and prevalence of positive or suspected cases of COVID-19, higher rate of out-of-pocket payments and lack of medical record systems [39]. Other studies such as Sumner et al 2022) also reported similar findings from the negative effects of the pandemic on the COC for chronic patients and emphasized the necessity of appropriate actions by health systems to ensure the routine care of these patients during health disasters [40][41][42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 88%
“…Several studies also showed that during the COVID-19 pandemic, the need and vital role of self-care behaviors in saving lives was more important. Using some life-saving self-care interventions with patients such as wearing masks, social distancing, have been an asset during COVID-19 periods of lockdown [3,8,25,26,27].…”
Section: Resultsmentioning
confidence: 99%